Pengaruh media gambar dan video serta motivasi terhadap kemampuan menceritakan kisah Qarun sebagai implementasi menghindari sifat kikir dan serakah dalam kehidupan sehari-hari pada siswa kelas V mata pelajaran SKI di MI Al Muhsinun Kauman Kota Mojokerto - Buro, Hasan HA (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
The purpose of this study are: 1) Describe the influence of media images and video media on the ability to tell the story of Qarun as implementation to avoid the miserly and greedy nature in the daily life of the students of class V subjects History of Islamic Culture in MI Al Muhsinun Kauman Mojokerto. 2) Describe the difference of motivation of students who are taught by the media of picture and video on the students of class V subjects History of Islamic Culture in MI Al Muhsinun Kauman Mojokerto City 3) Describe the interaction of image and video media as well as motivation to the ability to tell the story of Qarun as implementation avoid the miserliness and Greedy in everyday life on V grade students subjects History of Islamic Culture in MI Al Muhsinun Kauman Mojokerto City. This research is a survey type research with quantitative approach. The population as the object of research is the students of class V MI Al Muhsinun Kauman Mojokerto City, This research is included in comparative explanation research. Comparative research is a study that is comparing two or more variables. Data collection technique using questionnaire, while the data analysis technique using multiple linear regression analysis, with hypothesis test using t test and F test. From the analysis result can be concluded as follows: 1) There is influence of image media and video media to the ability to tell Qarun's story as an implementation avoids the miserly and greedy nature of everyday life of V-class students of Islamic Culture History in MI Al Muhsinun Kauman Mojokerto, where the ability to tell the story of Qarun as an implementation avoids the miserliness and greediness in the daily life of students with media Video from higher than the image media with a score of 176.82> 149.85. 2) There is a difference of motivation of students who are taught by the media of picture and video on V class student of Islamic Culture History lesson in MI Al Muhsinun Kauman of Mojokerto City, where the result of learning Islamic Culture History of low motivated student with score 96.15 lower than the learning result History Islamic culture of highly motivated students with a score of 97.61.3) There is an interaction of 49.2% between the media images and video media as well as the motivation of the ability to tell the story of Qarun as implementation avoid the miserly and greedy nature in everyday life in grade V students subjects History of Islamic Culture in MI Al Muhsinun Kauman Mojokerto